Belize. Technical cooperation strategy 2011-2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
It presents the IICA Belize country strategy, which is an instrument that sorts and prioritizes the technical cooperation that the institute offers to the country. The development of this strategy, a series of meetings and interviews were carried out, with both public and private sector and academia. In these sessions the following were analyzed: Review of current policies, priorities and objectives of the government for agricultural and rural development, Identification of the major challenges and opportunities for Belize's agricultural and rural sector, Identification of IICA's major capacities to deliver its technical cooperation services effectively and Elaboration of the Country Strategy 2011-2014.